Gradual transitions in morphology of diamond films grown by using N-2 admixtures of CH4+H-2 gas in a hot filament assisted chemical vapour deposition system - Kshirsagar, S. T.; Kshirsagar, R. B.; Patil, P. S.; Kulkarni, A.; Mandate, A. B.; Gaikwad, A. B.; Gokhale, Suresh P. (Diamond and Related Materials, 2005)
A study of the evolution of morphology of diamond films grown as a function of N-2 gas additions to the CH4+H-2 precursor in an HF-CVD system is presented. With the increase of admixture of N2 fraction, in contrast to earlier studies, the morphology was observed first to gradually change from {111}-faceted crystallites texture to that of an intermediate cubo-octahedral crystallite texture and then gradually but finally to transform completely into that of {100}-faceted crystallites. The threshold nitrogen concentration, [N-2](thr), required to bring about the said transition in morphology was much larger than it was reported previously. Moreover, the morphology transition required a larger [N-2](thr) when a large fraction of methane was employed. Further additions of nitrogen, that just exceeded the [N-2](thr), resulted in growth of films containing slightly bigger {100}-multi-layered grains or isolated planar {100}-platelets. For extremely large nitrogen additions, the growth of nanocrystalline or amorphous carbon films was observed. The N-2 additions more than 50 vol.% did not yield any deposition. Raman scattering and photoluminescence measurements were used respectively for characterizing the quality and nitrogen doping in the films. These results are attributed to the possible catalytic role of atomic nitrogen at the growing surface. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: diamond film; hot filament CVD; morphology transitions; nitrogen

N,S-Co-doped TiO2 Nanophotocatalyst: synthesis, electronic structure and photocatalysis - Sathish, M.; Viswanath, R. P.; Gopinath, Chinnakonda S. (Journal of Nanoscience and Nanotechnology, 2009)
N,S-co-doped anatase-phase TiO2 (N,S-TiO2) nanophotocatalysts were prepared from either benzothiazoline or aminothiol with titanium isopropoxide followed by a systematic thermal decomposition. The chemical nature of S and N in N,S-TiO2 have been identified by XPS to be sulfate and NO-like, respectively. A significant band broadening and red-shift in the UV-visible absorption spectrum of N,S-TiO2 suggests a band gap reduction compared to TiO2. A maximum band-gap narrowing of 0.22 +/- 0.02 eV was observed on N,S-TiO2. Higher energy width observed on N,S-TiO2 is in contrast to 0.13 eV from N-doped TiO2 indicating the sulfate-like species might play a major role in narrowing the band-gap to a Higher level. It is confirmed that the oxidation of N and S to NO and SO42- occurs in the final stage of preparation of N,S-TiO2, during calcination in air. It is predicted that the oxygen associated with sulfate and NO structural features could be crucial in bringing down the energy gap and red shift in optical absorption and the role of sulfur is to facilitate the above. Photocatalytic decomposition of methylene blue has been carried out on N,S-TiO2 shows higher activity than the commercial TiO2 in the visible region. However, sulfate species seems to enhance the activity of N,S-TiO2 marginally compared to N-TiO2, and possible suggestions are given to improve the same.
Keywords: nitrogen; Photocatalyst; Sulfur; TiO2; Visible Light Absorption

NOx reduction at near ambient temperatures and under lean-burn conditions on modified pd surfaces - Roy, Kanak; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
Palladium surfaces that are modified with O atoms in the subsurface broaden the NO reduction temperature regime up to 325 K with O-2-rich NO+H-2+O-2 compositions. Compared to virgin Pd surfaces, up to 150% higher deNO(x) catalytic activity was observed with modified Pd surfaces at the reaction maximum. Molecular beam instrument and ambient-pressure photoelectron spectroscopy were employed to follow the kinetic and surface changes. These results open up a possibility to realize the cold-start reduction of NOx (deNO(x)). DeNO(x) activity reported in the literature with supported Pd catalysts after a simple calcination in air compares well with our present observations. Surface modification is likely to demonstrate a high potential for other catalytic reactions at relatively low temperatures.
Keywords: heterogeneous catalysis; nitrogen; oxygen; Palladium; surface chemistry

Resorcinol-Azodianiline Covalent Organic Framework Supported FeOOH Quantum Dot-Catalyzed Electrochemical Ammonia Synthesis under Ambient Conditions - Shekhar, Pragalbh; Kosugi, Kento; Singh, Himan Dev; Kushwaha, Rinku; Rase, Deepak; Matsuzaki, Takumi; Jain, Chitvan; Singh, Piyush; Singh, Yashraj; Vinod, Chathakudath Prabhakaran; Kondo, Mio; Masaoka, Shigeyuki; et al. (CHEMISTRY OF MATERIALS, 2024)
Keywords: conversion; nitrogen; Recent Progress; reduction